Hubungan Status Lingkar Lengan Atas Ibu Hamil dengan Antropometri Bayi Baru Lahir di Sumatera Barat, Indonesia: The Relationship between Mid Upper Arm Circumference and Newborn Anthropometry Outcomes in West Sumatera, Indonesia - Mulyono, Andriani; Aji, Arif Sabta; Irwanti, Winda; Afifah, Effatul; Lipoeto, Nur Indrawaty (Amerta Nutrition, 2024)
Background: Mid-upper Arm Circumference (MUAC) during pregnancy is used to determine Chronic Energy Deficiency (CED). Pregnant women with CED are at risk of giving birth with Low Birth Weight (LBW), short, and wasting babies. Data from the West Sumatra Health Office show that the number of women suffering from continues to increase. The percentage of LBW per 1000 live births is also high and has not decreased significantly. Objectives: To determine the relationship between MUAC and newborn anthropometry outcomes in West Sumatera, Indonesia. Methods: This research used secondary data from the VDPM Cohort Study with 184 pairs of mothers and babies. The variables taken in this study were MUAC, Birth Weight (BWG), Birth Body Length (BLG), Birth Head Circumference (HDC), and Small for Gestational Age (SGA). Data analysis used descriptive analysis, Spearman Correlation, and Wilcoxon tests. Results: There was a significant positive correlation between MUAC and the anthropometry of newborn babies (p-value<0.05, for all comparisons). The greater the MUAC, the greater the anthropometry outcomes. However, the correlation was weak. There was a significant relationship between MUAC and SGA (p-value≤0.001). Babies with appropriate gestational age (AGA) had normal MUAC status and women who had CED status most likely gave birth to a baby with an SGA status. Conclusions: The MUAC status of pregnant women determines newborn anthropometry outcomes. Therefore, mothers can prepare for pregnancy by maintaining their health and nutritional status. Further studies are needed to confirm these findings.